2019
DOI: 10.2209/tdcpublication.2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Parental Satisfaction with Ambulatory Anesthesia during Dental Treatment for Disabled Individuals and Their Preference for Same in Future

Abstract: The purpose of this study was to survey parental satisfaction with ambulatory anesthesia during dental treatment in disabled patients. Factors associated with parental preference for general anesthesia during future dental treatment in such patients were also investigated. A questionnaire was mailed to the parents of 181 disabled individuals who underwent dental treatment under ambulatory anesthesia at Tokyo Dental College Suidobashi Hospital between 2012 and 2016. A total of 71 responses were received (39.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
(19 reference statements)
0
9
0
4
Order By: Relevance
“…Prior experience to GA decreases fear in parents which Ohtawa et al [ 24 ] has shown while their risk evaluation remains unaffected. As parent’s knowledge significantly correlates with their risk evaluation ( p < 0.00) practitioners should focus on educating their patients in terms of likelihood of complications during or after GA.…”
Section: Discussionmentioning
confidence: 99%
“…Prior experience to GA decreases fear in parents which Ohtawa et al [ 24 ] has shown while their risk evaluation remains unaffected. As parent’s knowledge significantly correlates with their risk evaluation ( p < 0.00) practitioners should focus on educating their patients in terms of likelihood of complications during or after GA.…”
Section: Discussionmentioning
confidence: 99%
“…The indication for GA is depended on the severity of disability (Maestre, 1996, Norderyd et al, 2017. Mentally disabled paediatric patients did not show higher complication rates which leaves GA as a reasonable and safe option (Bartella et al, 2018, Ohtawa et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…5 Children with sensory integration differences receive preoperative sedation that deviates from standard practice more often than the general pediatric population and experience a significant proportion of anesthetic inductions judged by parents as "not smooth." 7,8 Anesthetic induction in these children merits special consideration. It is unclear whether FP would improve the procedural experience for children with unique sensory integration needs.…”
Section: Patient-and Family-centered Carementioning
confidence: 99%